Hypertensive disorders of pregnancy in women with structural heart disease: data from the ESC EORP Registry of Pregnancy and Cardiac disease (ROPAC). (14th October 2021) - Ramlakhan, K P; Malhame, I; Marelli, A; Rutz, T; Goland, S; Johnson, M R; Hall, R; Cornette, J M J; Roos-Hesselink, J W; ,
Abstract: Background: Hypertensive disorders of pregnancy (HDP) are estimated to occur in 10% of pregnancies in the general population and preeclampsia specifically in 3–5%. HDP are suggested to be more common in and less well tolerated by women with heart disease. However, the current data are conflicting and this knowledge gap impacts clinical practice guidelines. Purpose: To harness the well characterized data of the Registry of Pregnancy and Cardiac disease (ROPAC) to examine the frequency of HDP in women with structural heart disease and its impact on maternal and perinatal outcomes. Methods: The ROPAC registry (n=5739) is a worldwide prospective registry on pregnancies in women with heart disease, including congenital heart disease (CHD, n=3295), valvular heart disease (VHD, n=1648), cardiomyopathy (CMP, n=438), aortopathy (AOP, n=217), ischemic heart disease (IHD, n=95), and pulmonary arterial hypertension (PAH, n=45). We defined HDP as either chronic hypertension, gestational hypertension, and/or preeclampsia (including HELLP syndrome and eclampsia) and assessed the frequency of HDP in each heart disease category. Predictors of preeclampsia were identified using multivariable logistic regression. The proportion of women with adverse maternal, pregnancy, and fetal/neonatal outcomes were described among women with preeclampsia or HDP, and compared between women with and women without HDP using chi-square tests. Results: In total, the frequency of HDP and preeclampsia was 9.3% and 2.6% in CHD, 7.5% and 2.2% in VHD, 18.7% and 7.1% in CMP, 15.7% and 2.8% AOP, 35.8% and 6.3% in IHD, and 22.2% and 11.1% in PAH. Independent predictors of preeclampsia were chronic hypertension (OR 3.06, 95% CI 2–4.69), nulliparity (2.39, 1.68–3.38), HDP in a previous pregnancy (2.29, 1.11–4.7), gestational diabetes in the current pregnancy (2.13, 1.13–4.03), pulmonary hypertension (1.71, 1.08–2.7) and age (1.04, 1.01–1.07). In women with preeclampsia and heart disease, maternal mortality was 3.5% and heart failure was 29.1%. Maternal mortality (1.4% vs 0.6%, p=0.042), heart failure (18.5% vs 10.6%), Caesarean section (61.2% vs 48.4%), preterm births (27.4% vs 16.9%), low Apgar score (9.8% vs 6.6%), small for gestational age (14.6% vs 9.7%) and neonatal mortality (1.7% vs 0.4%) were higher in women with than women without HDP (all p<0.001 except maternal mortality). Conclusions: The frequency of HDP is increased (>10%) in CMP, AOP, IHD and PAH, but not in CHD and VHD. The high frequency of HDP is partly due to chronic hypertension, but the incidence of preeclampsia is also increased (>5%) in CMP, IHD and PAH. Among women with cardiac disease, HDP were associated with adverse maternal and perinatal outcomes. The high maternal mortality rate of 3.5% in women with heart disease and preeclampsia warrants close clinical monitoring and a better understanding of the optimal management strategies in the complex population group. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): Funding from "Zabawas Foundation" and "De Hoop Foundation" in addition to the support from EORP is greatly acknowledged. Since the start of EORP, the following companies have supported the programme: Abbott Vascular Int. (2011–2021), Amgen Cardiovascular (2009–2018), AstraZeneca (2014–2021), Bayer AG (2009–2018), Boehringer Ingelheim (2009–2019), Boston Scientific (2009–2012), The Bristol Myers Squibb and Pfizer Alliance (2011–2019), Daiichi Sankyo Europe GmbH (2011–2020), The Alliance Daiichi Sankyo Europe GmbH and Eli Lilly and Company (2014–2017), Edwards (2016–2019), Gedeon Richter Plc. (2014–2016), Menarini Int. Op. (2009–2012), MSD-Merck & Co. (2011–2014), Novartis Pharma AG (2014–2020), ResMed (2014–2016), Sanofi (2009–2011), Servier (2009–2021), Vifor (2019–2022).